Dampak Pewarna Ekstrak Etanol Buah Naga Merah (Hylicerius polyhizus) terhadap Lip Balm Minyak Bunga Kenanga (Cananga oil) - Debi Meilani; Suprianto Suprianto; Samran Samran (Jurnal Indah Sains dan Klinis, 2024)
Background: Red dragon fruit holds promise as a natural dye alternative due to its anthocyanin content. Objective: This study aimed to evaluate the potential of ethanol extract from red dragon fruit as a dye in Lip Balm formulations and investigate how varying the concentration of this extract affects the formula. Method: The study involved extracting the dye from red dragon fruit and incorporating it into a Lip Balm preparation using natural fruit-based dyes. Results: The findings indicated that the red dragon fruit extract yielded favorable results after undergoing various tests, including organoleptic evaluation, homogeneity, melting point, irritation, and user preference. Conclusion: The extract of red dragon fruit can be utilized as a dye in Lip Balm formulations. The resulting colors range from pink to dark red, with higher concentrations of the extract producing more intense colors in the final Lip Balm product containing ylang-ylang flower oil (Cananga oil)